The interdomain flexible linker of the polypeptide GalNAc transferases dictates their long-range glycosylation preferences - De Las Rivas, Matilde (2020)
We thank synchrotron radiation sources DLS (Oxford) and in particular beamline I03 (experiment number MX10121-7). We thank ARAID, MEC (CTQ2013-44367-C2-2-P, BFU2016-75633-P, CTQ2015-67727-R, CTQ2015-70524-R, and RYC-2013-14706), the National Institutes of Health (GM113534, and instrument grant GM113534-01S), the Danish National Research Foundation (DNRF107), the FCT-Portugal (UID/Multi/04378/2013 and PTNMR Project No 022161), and the DGA (B89) for the financial support. I.C. thanks Universidad de La Rioja for the FPI grant. F.M. thanks FCT-Portugal for IF Investigator. E.L.-N. acknowledges her postdoctoral EMBO fellowship ALTF 1553-2015 co-funded by the European Commission (LTFCOFUND2013, GA-2013-609409) and Marie Curie Actions. H.C. and J.J.-B. thank EU for the TOLLerant project. The research leading to these results has also received funding from the FP7 (2007-2013) under BioStruct-X (grant agreement No. 283570 and BIOSTRUCTX_5186). We also thank BIFI (Memento cluster) and CESGA for computer support.